Influence of Algal Incorporation on Sensory and Physicochemical Attributes of Caseless Sausage—Ćevap (CSC) - Caba Siladji; Vesna Djordjevic; Branka Borovic; Volker Heinz; Nino Terjung; Nenad Katanic; Igor Tomasevic (Foods)
This study explores the influence of algal incorporation on the sensory and physicochemical attributes of caseless sausage—ćevap (CSC). Various algae, including Chlorella vulgaris, Himanthalia elongata (sea spaghetti), and Undaria pinnatifida (wakame), were added at different concentrations to standard CSC formulations. Proximate analysis revealed that the addition of algae did not significantly change crude protein and fat content (p > 0.05). Furthermore, sea spaghetti and wakame resulted in lower moisture levels and decreased cooking loss, while all algae varieties raised the salt content (p < 0.05) due to their inherent sodium levels. Texture analysis demonstrated that the inclusion of sea spaghetti and Chlorella led to reductions in hardness and chewiness, while wakame resulted in a firmer texture, highlighting its substantial impact on textural attributes. Color measurements indicated that wakame significantly affected the color profile (p < 0.05), resulting in decreased lightness and increased darkness in the sausage, surpassing the effects of other algae. Sensory evaluations showed that formulations containing wakame received the lowest scores for color, smell, taste and overall acceptability—up to 1.5 points lower compared to the control samples. On the other hand, some formulations with other algae showed promising small deviations from the control. Overall, this research supports the viability of using algae as functional ingredients in meat products, emphasizing the importance of selecting the appropriate type and concentration of algae to optimize both physicochemical parameters and sensory qualities in caseless sausages.